PECULIARITIES AND PROCEDURE FOR PILOT DECISION OF EUROPEAN COURT OF HUMAN RIGHTS - Григоренко, Артем Олегович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
As the title implies the article describes pilot decisions of the European Court of Human Rights and relevance pilot decisions for the Ukrainian legislation. In the process of emergence as a European state, Ukraine needs effective enforcement decisions of the European Court of Human Rights. The decisions of European Court in lawsuits against Ukraine protect human rights. By the court decision Ukraine is obliged to pay monetary compensation. The pilot decisions of European Court of Human Rights play an important role. The pilot decisions aimed at improving Ukrainian legislation and will oblige Ukraine state to pay money to a person for the damage done. Moreover, executing a pilot decision, Ukraine passed the law «On the state guarantees regarding the enforcement of court decisions» of 05 June 2012. This law establishes state guarantees for the implementation of court decisions on the recovery of funds from the debtor. The debtor is a state agency. So Ukraine complied the provisions of the Convention for the Protection of Human Rights and Fundamental Freedoms. The Cabinet of Ministers of Ukraine adopted the resolution № 440 «On approval of debt repayment by court decisions, and enforcement of which is guaranteed by the state» of 03 September 2014. Purpose: to carry out a comprehensive description of the pilot decisions of the European Court of Human Rights. Investigate the legal regime of pilot decisions adopted by the European Court of Human Rights in lawsuits against Ukraine and evaluate their impact on amendments to current legislation. Research methods: used methods of analysis, comparison and synthesis, theoretical and legal modeling, cognitive-analytical and data collection systems. The results: obtained the conclusion that the pilot decision of the European Court of Human Rights requires the Ukrainian state to make changes to Ukrainian legislation. Discussion: the necessity of developing law project to legislation of Ukraine having regard decisions of the European Court of Human Rights. Moreover, there is a need to develop new draft legal acts of Ukrainian legislation.